Viability of Hopea Parviffora Seeds With Reference to Temperature , Medium of Storage and Microencapsulation Techniques - Sunilkumar K K (Department of Silviculture and Agroforestry, College of Forestry, 1996)
A detailed study was conducted at College of Forestry, Kerala Agricultural university, Vellanikkara, Thrissur, Kerala during 1994 – 95 to study the effect of temperature, storage medium, fungicide and microencapsulation of zygotic embryo (synthetic seed) on the storage behaviour of Hopea parviflora seeds. Storing the dewinged seeds with a moisture content below 30 per cent resulted in rapid decline in seed viability due to dehydration injuries irrespective of storage temperature. Sand and neemcake was inappropriate as a storage medium because sand favoured early germination of the seeds in storage condition itself and neemcake caused severe desiccation injuries. Storing fungicide treated winged seeds collected just before natural seedsheding, at 100 C retained high germination percentage upto 40 days. Sythetic seeds were also successfully stored up to 1 month at 100C without significant reduction in germination percentage. Two ppm and three ppm ABA was observed to be helpful for maintaining higher germination percentage of synthetic seeds during storage.